MOBILE AND ELECTRONIC MEDICAL SUPPORT AND EDUCATION FOR DYSLEXIC STUDENTS - VIRVOU, MARIA; ALEPIS, EYTHIMIOS (Mathematical Methods In Scattering Theory And Biomedical Engineering, 2006)
In standard educational systems of many countries dyslexic students are considered as a special category of students that should be given special care so that they may be helped with their dyslexia problems. Such opportunities should be given to dyslexic users through educational software as well. In this paper we describe an integrated educational system that supports dyslexic students through multiple facilities.